A protocol for the delimitation of areas of endemism and the historical regionalization of the Brazilian Atlantic Rain Forest using harvestmen distribution data. (13th May 2015) - DaSilva, Marcio Bernardino; Pinto‐da‐Rocha, Ricardo; DeSouza, Adriano Medeiros
Abstract: The concept of areas of endemism (AoEs) has rarely been discussed in the literature, even though the use of methods to ascertain them has recently increased. We introduce a grid‐based protocol for delimiting AoEs using alternative criteria for the recognition of AoEs that are empirically tested with harvestmen species distributions in the Atlantic Rain Forest. Our data, comprising 778 records of 123 species, were analysed using parsimony analysis of endemicity and endemicity analysis on four different grids (two cell sizes and two cell placements). Additionally, we employed six qualitative combined criteria for the delimitation of AoEs and applied them to the results of the numerical analyses in a new protocol to objectively delimit AoEs. Twelve AoEs (the most detailed delimitation of the Atlantic Rain Forest so far) were delimited, partially corroborating the main divisions previously established in the literature. The results obtained with the grid‐based methods were contradictory and were plagued by artefacts, probably due to the existence of different endemism patterns in one cell or to a biogeographical barrier set obliquely to latitudinal and longitudinal axes, for example. Consequently, the congruence patterns found by them should not be considered alone; qualitative characteristics of species and clade distributions and abiotic factors should be evaluated together. Mountain slopes are the main regions of endemism, and large river valleys are the main divisions. Refuges, marine transgressions and tectonic activity seem to have played an important role in the evolution of the Atlantic Rain Forest.